Global Palestine: International Solidarity and the Cuban Connection. Issue 2 (November 2019) - Henry, Robert Austin
Abstract : Since the Left turn of the late 1990s, most Latin American and Caribbean nations have come to support the Palestinian struggle for statehood and the right of return, opposing Israel's and its allies' severe repression of them. This study explains the singular historic exception — Cuba's 70-year-long solidarity with Palestine — through the theoretical lenses of race, class and colonialism. It first reviews the transformation of Cuba's constrained solidarity with Palestine in the pre-revolution post-war years to comprehensive internationalism from Socialist Cuba. Then, analysing Zionism and its Latin American advocates from partition in 1947, we assess Cuba's break with Israel in 1973, alongside US-based Israeli and Cuban expat hostilities.